Effect of Organotin tributyltin chloride on Oxygen consumption of Macrobrachium kistnensis - K.B. Shejule, B.C. Ghoble, P.S. Kharat, Laxmi B. Ghoble, (Journal of Phytology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Aquatic animalÃ¢â‚¬â„¢s responses to chemical pollutants in the aquatic environment are usually understood, through determining their rate of survival and changes in the levels of various physiological phenomenonÃ¢â‚¬â„¢s. In the present study effect of LC50 for 48 hrs of Organotin tributyltin chloride on the rate of oxygen consumption of freshwater prawn, Macrobrachium kistnensis has been determined. The prawns were exposed to lethal concentration of 0.26 ppm of organotin tributyltin chloride and oxygen consumption rate was measured after 1, 2, 4, 8, 12 and 24 hrs of exposed period. The obtained data showed that there was an increase in the rate of oxygen consumption in Macrobrachium kistnensis, when exposed for 1 and 2 hrs to 0.26 ppm of TBTCl, where as the rate of oxygen consumption decreased significantly (P<0.05) after exposed for 4 to 24 hrs at 0.26 ppm as compared to control values. The increases in oxygen consumption in 1 and 2 hrs indicated immediate response to the toxic environment and initial elevation in the rate of oxygen consumption showed a compensatory phase to enhance the physiological activity, but the steady decrease may be due to the failure of respiratory metabolism in Macrobrachium kistnensis.